Exploring research priorities for the IPCC Seventh Assessment Report - Institute,G (Grantham Institute, Imperial College London, 2025)
Following the IPCC approval of the outlines for its three Working Group contributions to the Seventh Assessment cycle, the Grantham Institute hosted a day-long event bringing together experts from across the UK climate research community to discuss the Working Group outlines and explore research priorities to strengthen and support the IPCC assessment. This report aims to signpost some key areas that would benefit from further research to deliver robust IPCC assessment findings.